Impact of comorbidities on mortality in hospitalized influenza patients with diabetes – Analysis of the Austrian Health Insurance. (April 2021) - Aziz, Faisal; Aberer, Felix; Moser, Othmar; Sourij, Caren; von Lewinski, Dirk; Kaser, Susanne; Reichardt, Berthold; Sourij, Harald
Abstract: Aims: To assess the impact of characteristics and comorbidities on the hospitalization rate and 30- and 90-days all-cause mortality after hospitalization for influenza-related illness (IRI) in individuals with diabetes. Methods: Data of 507, 184 individuals with diabetes enrolled in the national Austrian Health Insurance database during 2013–2017 were analyzed. Hospitalization for IRI was defined as per International Classification of Disease 10 codes (J09, J10, J11). All-cause mortality was calculated for 30- and 90-days post-hospitalization. Results: Of the total diabetes population, 1994 (0.4%) were hospitalized for IRI during 2013–2017. The rate of comorbidities was higher in individiuals who were hospitalized due to IRI as compared with the general diabetes population. Overall 30-days cumulative mortality following hospitalization for IRI was 7.9% and 90-days mortality was 10.3%. The risk (adjusted Hazard Ratio, 95% Confidence Interval) of IRI related 90-days mortality increased with age (50–59: 3.00, 0.65–13.94; 60–69: 4.16, 0.99–17.55; 70–79: 4.79, 1.16–19.76; 80+: 7.15, 1.74–29.46), heart failure (1.97, 1.31–2.98), renal disease (1.50, 1.05–2.14), and Charlson comorbidity index (1.14, 1.08–1.19). Conclusions: Older age, heart failure, renal disease, and Charlson comorbidity index were significant predictors of mortality following hospitalization for IRI in individuals with diabetes. These findings could help in improving the clinical management and performance of surveillance and health systems concerning IRI in Austria.